Analisis Pemasaran Komoditas Cabai Rawit Merah di Desa Brajan, Kecamatan Prambanan, Kabupaten Klaten - Hastuti Hastuti; Asri Nidya Angga Sari (Jurnal Ilmu Pertanian Indonesia, 2020)
Klaten District is one of the producers of red cayenne pepper in Indonesia. Brajan Village is one of the villages in Prambanan District that produces red cayenne pepper. Brajan Village has a strategic location, which is near the border of Central Java province, so it has a very diverse marketing channel for red cayenne pepper. The number of marketing channels affects the price at the consumer level which affects the marketing margin. This research aims are: to analyze the comparison of member farms with non member farmer groups of red cayenne pepper, to analyze the channels and functions of the red cayenne pepper marketing, and to analyze the efficiency of the red cayenne pepper market in Brajan Village, Prambanan Sub-District, Klaten District. The analysis methods used are income analysis, R/C ratio analysis, analysis of channel and function marketing, marketing margin analysis, farmer's share analysis, B/C ratio analysis, and analysis of price transmission elasticity. The results showed that the income of red cayenne pepper farming at the cash cost of member farmers and non-member farmer groups are profitable. Income on total costs to member farmers is profitable, while non member farmers are losses. There are 12 marketing channels for red cayenne pepper in Brajan Village, and the marketing channels in the form of farmers to sub district collectors to retail traders to final consumers are the most efficient marketing channels. Keywords: B/C ratio, farmer's share, marketing channel, marketing margin, price transmission elasticity